2019
DOI: 10.3390/jcm8101682
|View full text |Cite
|
Sign up to set email alerts
|

Disordered Eating Behaviours and Eating Disorders in Women in Australia with and Without Polycystic Ovary Syndrome: A Cross-Sectional Study

Abstract: Psychological co-morbidities common in polycystic ovary syndrome (PCOS) may contribute to disordered eating and subsequent weight gain. This cross-sectional study aimed to determine the prevalence of disordered eating and a range of eating disorders and demographic risk factors associated with these behaviours within an Australian group of women with and without PCOS. Data from 899 women with (n = 501) and without (n = 398) PCOS were analysed as possibly indicative of disordered eating or eating disorders usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 64 publications
0
41
0
1
Order By: Relevance
“…A recent Australian study explored the cross-sectional relationship between disordered eating or eating disorders and a range of demographic risk factors (PCOS diagnosis, body mass index [BMI], age, country of birth). Authors reported that disordered eating, but not eating disorders, were more prevalent in women with PCOS when compared with controls [57]. Of the disorders, binge-eating disorder (BED) was the most commonly reported but not significantly different to controls.…”
Section: Eating Disordersmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent Australian study explored the cross-sectional relationship between disordered eating or eating disorders and a range of demographic risk factors (PCOS diagnosis, body mass index [BMI], age, country of birth). Authors reported that disordered eating, but not eating disorders, were more prevalent in women with PCOS when compared with controls [57]. Of the disorders, binge-eating disorder (BED) was the most commonly reported but not significantly different to controls.…”
Section: Eating Disordersmentioning
confidence: 97%
“…BED is the most common form of eating disorders within the general population and may explain the frequency and lack of significance between the two groups [58]. The crosssectional study also reported higher BMI and older age increased the odds of disordered eating whilst increased BMI and younger age increased the odds of an eating disorder [57]. It is important to highlight that the controls were psychology university students and may not be a true representation of the general population.…”
Section: Eating Disordersmentioning
confidence: 99%
“…This highlights that lean women with PCOS have an intrinsic IR, 43 which is compounded by an extrinsic/lifestyle-related IR in overweight/obese women with PCOS. 7,8 Finally, chronic inflammation is known to contribute to HA among women with PCOS, which itself has been reported to exacerbate hyperglycemia. [106][107][108] Cellular stress triggers cellular inflammation, causing immunity cells to mitigate, infiltrate, and amplify β-cells inflammation.…”
Section: Risk Of T2dm In Polycystic Ovary Syndromementioning
confidence: 99%
“…1-3 PCOS is associated with a variety of reproductive, 4 metabolic, 5 and psychological symptoms. [6][7][8] Women diagnosed with PCOS are also likely to experience excess weight, with 60% being overweight or with obesity. 9 The exact etiology of PCOS is yet to be determined; however, insulin resistance (IR) and hyperandrogenism (HA) are thought to underpin the disorder, all of which are exacerbated by obesity.…”
mentioning
confidence: 99%
“…2 Women with PCOS could experience a range of symptoms, including metabolic, reproductive and psychological health challenges. [3][4][5][6][7][8] There are also longer-term health consequences, such as increased risks of metabolic syndrome, type 2 diabetes and cardiovascular disease. 4,9 Women with PCOS are more likely to be overweight and obese compared with age-matched controls.…”
mentioning
confidence: 99%